Geomorphological effects of the 1840 Ahora Gorge catastrophe on Mount Ararat (Eastern Turkey) - Roberto Sergio Azzoni; Davide Fugazza; Carlo Alberto Garzonio; Kathleen Nicoll; Guglielmina Adele Diolaiuti; Manuela Pelfini; Andrea Zerboni (Geomorphology, 2019)
Ahora Gorge is a 400 m deep canyon located along the North Eastern flank of Mt. Ararat (Turkey), a compound volcanic complex covered by an ice cap. In the past, several diarists and scientific authors reported a calamitous event on July 2, 1840, when a landslide triggered by a volcanic eruption and/or an earthquake obliterated several villages located at the foot of the volcano. The reasons and effects of this Ahora Gorge Catastrophe (AGC) event have been obscure and ambiguous. To reappraise the 1840 catastrophe and the geomorphic evolution of the Ahora Gorge, we used high-resolution satellite images, remote sensing thermal data supplemented by observations collected during two field surveys. According to our interpretation, an earthquake in 1840 triggered an abrupt volcanic eruption, which caused the consequent rapid melting of glacial ice and mountain snow. This event produced significant mud and ice flow along the Ahora Gorge that inundated the villages downslope. The flooding, which we interpret as a lahar, deposited a wide alluvial fan at the foot of the volcano. Today, an elongated landform present within the Ahora Gorge has alternately been interpreted as a landslide deposit. Ourmulti-data integrated analysis and ground-based observations demonstrate that this feature is an unmapped glacier. The shape of the landform coupled with ASTER thermal satellite data and ground-based observations reveal that a debris-covered glacier (DCG) formed soon after the catastrophic lahar. Our discovery of the Ahora Gorge Glacier in context of a reappraisal of the Ahora Gorge Catastrophe demonstrates the contribution of glaciers in shaping the landscape near ice-capped volcanoes. Moreover, our data underscore the importance of being more aware of the potential future geo-hazards posed by Mount Ararat, particularly where glaciers are still present along several valleys and seismically-induced lahar events might occur.